Предмет: Алгебра,
автор: Hilson
помогите упростить выражение(2x−3)(3x+7)−(x−5)(5x+6)−x2 и вычислить его значение при х=11/24
Ответы
Автор ответа:
0
(2x-3)(3x+7)-(x-5)(5x+6)-x^2=
=6x^2+14x-9x-21-(5x^2+6x-25x-30)-x^2=
=6x^2+14x-9x-21-5x^2-6x+25x+30-x^2=
=24x+9
При x=11/24
24*11/24+9=11+9=20
=6x^2+14x-9x-21-(5x^2+6x-25x-30)-x^2=
=6x^2+14x-9x-21-5x^2-6x+25x+30-x^2=
=24x+9
При x=11/24
24*11/24+9=11+9=20
Похожие вопросы
Предмет: Математика,
автор: andreic0schelev
Предмет: Математика,
автор: salikhkylovarufina
Предмет: История,
автор: deni973
Предмет: Математика,
автор: edifanovayulya
Предмет: Математика,
автор: anna200403028